Resistance to Bt Maize by Western Corn Rootworm: Effects of Pest Biology, the Pest–Crop Interaction and the Agricultural Landscape on Resistance - Gassmann, Aaron J. (Insects, 2021)
SIMPLE SUMMARY: Since the 1990s, an important innovation in the management of agricultural pest insects has been the commercial cultivation of genetically engineered crops that produce insecticidal toxins, which in turn act to protect plants from feeding injury by insects. To date, these transgenic crops, which include cotton, maize and soybean, have produced insecticidal proteins derived from the bacterium Bacillus thuringiensis (Bt). Benefits associated with planting of Bt crops include reduced feeding injury from pest insects, decreased yield losses from pests and less harm to the environment. However, the evolution of Bt resistance by insect pests can diminish these benefits. One serious insect pest currently managed with Bt maize is the western corn rootworm. The larval stage of this insect feeds on maize roots and can substantially reduce yield. In some parts of the US Corn Belt, western corn rootworm rapidly adapted to Bt maize, and currently, some populations show resistance to all commercially available Bt traits. This review summarizes the time course of resistance development in the field, key factors contributing to resistance evolution, and steps that biotechnology companies, farmers and regulatory agencies can take to delay additional cases of pest resistance to current and future transgenic technologies. ABSTRACT: The western corn rootworm, Diabrotica virgifera virgifera LeConte, is among the most serious pests of maize in the United States. Since 2003, transgenic maize that produces insecticidal toxins from the bacterium Bacillus thuringiensis (Bt) has been used to manage western corn rootworm by killing rootworm larvae, which feed on maize roots. In 2009, the first cases of field-evolved resistance to Bt maize were documented. These cases occurred in Iowa and involved maize that produced Bt toxin Cry3Bb1. Since then, resistance has expanded to include other geographies and additional Bt toxins, with some rootworm populations displaying resistance to all commercially available Bt traits. Factors that contributed to field-evolved resistance likely included non-recessive inheritance of resistance, minimal fitness costs of resistance and limited adult dispersal. Additionally, because maize is the primary agricultural crop on which rootworm larvae can survive, continuous maize cultivation, in particular continuous cultivation of Bt maize, appears to be another key factor facilitating resistance evolution. More diversified management of rootworm larvae, including rotating fields out of maize production and using soil-applied insecticide with non-Bt maize, in addition to planting refuges of non-Bt maize, should help to delay the evolution of resistance to current and future transgenic traits.